2022
DOI: 10.4103/jrms.jrms_921_21
|View full text |Cite
|
Sign up to set email alerts
|

Dermatologic problems associated with personal protective equipment in health-care workers managing COVID-19 patients

Abstract: Background: The safety of health-care workers (HCWs) during the COVID-19 pandemic is a major concern worldwide. Dermatological problems due to personal protective equipment are annoying issues. We aimed to evaluate dermatological adverse events following the use of these protections in HCWs managing COVID-19 patients. Materials and Methods: One hundred and fifty-six workers managing COVID-19 patients were enrolled in this cross-sectional study. We condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
1
0
0
Order By: Relevance
“…In this study, the area that was reported to be most frequently affected by skin complications related to face mask use was the nasal bridge (78.1%). This is supported by prior studies in the literature, including those of Daye et al (40.7 %) [9], Alizadeh et al (82.7 %) [11] and Gürlek and Özyürek (69.9%) [12]. The area with the second highest prevalence was the skin behind the ear (76.0%), which was also reported by Daye et al (28.4%) [9] and Gürlek and Özyürek (69.8%) [12].…”
Section: Discussionsupporting
confidence: 86%
“…In this study, the area that was reported to be most frequently affected by skin complications related to face mask use was the nasal bridge (78.1%). This is supported by prior studies in the literature, including those of Daye et al (40.7 %) [9], Alizadeh et al (82.7 %) [11] and Gürlek and Özyürek (69.9%) [12]. The area with the second highest prevalence was the skin behind the ear (76.0%), which was also reported by Daye et al (28.4%) [9] and Gürlek and Özyürek (69.8%) [12].…”
Section: Discussionsupporting
confidence: 86%